Response of growth, yield and root characteristics of a determinate cowpea variety to variable phosphorus fertiliser and lime application rates - Maphoto, Patrina Nare (My University, 2018)
Soil acidity is one of the abiotic stress factors that greatly limit the productivity of crops on farmers’ fields. A greenhouse study was carried out over two summer growing seasons to evaluate the effect of lime and phosphorus (P) application rates on the growth, yield and root attributes of a determinate cowpea variety on acid soil. The experiment was laid out as a 4x5 factorial arrangement with 4 replications. Treatment factors comprised of variable rates of Vaalburg dolomitic lime (0, 2, 4 and 6 t ha-1) and P (0, 15, 30, 45 and 60 kg ha-1) using single super phosphate, 10.5% P. The two treatment factors were combined resulting in a total of 20 treatment combinations. Data collected included cowpea growth parameters, crop phenology, yield attributes and root characteristics. While cowpea plants with no P application consistently gave the least plant height, stem diameter, number and length of trifoliate leaves, the 6 t ha1 lime rate appears to be completely disadvantaged for all measured parameters with generally lower values than in soil filled pots without lime application. Results showed that soil pH was increased with 6 t ha-1 lime application while soil electrical conductivity (EC), percent of organic matter (OM) and total organic carbon (TOC) were all increased with increasing P and lime rates. All measured cowpea growth attributes such as plant height, stem diameter, number of trifoliate leaves, and leaf area were significantly increased (p≤0.05) with increasing P and lime rates. During the two planting seasons, P and lime application resulted in reduced (p≤0.05) duration to flowering, pod formation and physiological maturity. The 6 t ha-1 lime application produced higher number of pods (2.50) compared to the other rates. Application rates of 45 kg P ha-1 and 6 t ha-1 of lime produced superior number of seeds per pod with high values of (13.71) and (12.85), respectively. However, cowpea root attributes namely number of nodules per plant, the third branching root diameter, angle of adventitious root, tap root diameter at 5 and 10 cm, shallow and deep score were significantly increased at moderate P rate of 30 kg P ha-1. Overall, findings of this study revealed that application of both P fertiliser and lime were able to ameliorate the negative effect of P deficiency from soil acidity on the evaluated cowpea variety and promoted increased yield. Keywords: Acid soil, grain cowpea, P fertiliser, lime, growth, root characteristics, yield
Thesis (MSc. Agriculture(Soil Science) -- University of Limpopo, 2018
Keywords: Acid soil; Grain cowpea; P fertiliser; Lime; Root characteristic; Soil acidity; Crops -- Effects of soil acidity on; Cowpea; Soils -- Phosphorus content